1999
DOI: 10.1099/13500872-145-7-1785
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence heterogeneity in the three copies of the long 16S–23S rDNA spacer of Enterococcus faecalis isolates

Abstract: The possibility of intragenic heterogeneity between copies of the long intergenic (1 63-235 rDNA) spacer region (LISR) was investigated by specific amplification of this region from 21 Enterococcus faecalis isolates. Three copies of the LlSR (rrnA, B and C) were demonstrated by hybridization of the LlSR to genomic DNA cleaved with I-Ceul and Smal. When the LISR amplicon was digested with Tsp5091, two known nucleotide substitutions were detected, one 4 nt upstream from the 5' end of the tRNAaIa gene (allele rrn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…These sequence data suggest that intraspecific diversity in the ISRs in C. difficile is much greater than that reported for any other bacterial species (4,5,12,15,17,20,27,30,40,50,51). Many authors have compared ISRs between different species and strains of a single bacterial species (15,17,33,44,46).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These sequence data suggest that intraspecific diversity in the ISRs in C. difficile is much greater than that reported for any other bacterial species (4,5,12,15,17,20,27,30,40,50,51). Many authors have compared ISRs between different species and strains of a single bacterial species (15,17,33,44,46).…”
Section: Discussionmentioning
confidence: 94%
“…In some cases the ISR diversity between species of a genus is lower than the diversity seen between the strains of C. difficile examined here. Sequence differences between ISRs of the same size most likely arise from nucleotide substitution events (4,5,25,30). Also, some ISRs were of similar length (e.g., rrnE and rrnF of S. aureus) but had sequence blocks with different nucleotide sequences, probably because of recombination events (25,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence and length polymorphisms found in the ITS are increasingly being used as tools for bacterial species and subspecies identification (17,27,29,37), typing (25,37), and evolutionary studies (1,12,33). Gürtler et al reported that ITS sequence analysis is complementary to the 16S rRNA gene for phylogenetic analysis (13). A PCR method based on ITS sequences has been developed for the detection and identification of K. pneumoniae subsp.…”
mentioning
confidence: 99%
“…The 16S-23S rDNA intergenic transcribed spacers (ITS) are the most variable regions of the ribosomal operon, and, apart from interoperonic nucleotide substitutions, insertions, and deletions, such ITS can be differentiated, given the presence of the different numbers and types of tRNA genes (9,10,31,49). Since the ITS have fewer functional constraints than the adjacent ribosomal genes, which undergo concerted evolution (17)(18)(19), their sequences can contain traces of ribosomal operon rearrangements and species-specific or even strain-specific traits that are useful for strain typing.…”
mentioning
confidence: 99%